Nonpsychotic Psychiatric Disorders in Juvenile Myoclonic Epilepsy - Polina V. Moskaleva; Olga S. Shilkina; Ivan P. Artyukhov; Irina G. Strotskaya; Diana V. Dmitrenko; Natalia A. Shnayder (International Journal of Biomedicine, 2017)
The association of epilepsy with mental illness has been described in recent years. Scientists are trying to relate certain epilepsies, such as juvenile myoclonic epilepsy (JME), with certain personality traits marked by emotional instability. The goal of this review is to evaluate the scientific literature about nonpsychotic psychiatric disorders in JME patients, the most common form of idiopathic generalized epilepsy (IGE). Data in this review were collected through an extensive literature search of available full-text publications in PubMed, Springer, Clinical Keys and eLIBRARY.RU databases. Comorbid personality and nonpsychotic psychiatric disorders are a common and interdisciplinary problem in JME management. The disorders in patients with JME often go undiagnosed and hence untreated. Therefore, this problem requires further and extensive investigation.